Composite TiC porous carbon as well as preparation method and application thereof

Porous carbon composites with TiC were prepared by in-situ polymerization, which solved the problems of insufficient mechanical strength and conductivity of porous carbon materials. It achieved uniform dispersion of TiC in porous carbon, improved the conductivity and mechanical strength of the material, and avoided pore collapse.

CN120841514APending Publication Date: 2025-10-28WANXIANG 123 CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511250821.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-03
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

Existing porous carbon materials have insufficient mechanical strength and conductivity, and TiC nanoparticles are prone to agglomeration when composited with the carbon matrix, resulting in poor dispersion, which leads to pore collapse and unsatisfactory conductivity during high-temperature calcination.

Method used

Porous carbon with composite TiC was prepared by in-situ polymerization. Phenolic resin was mixed with an organic titanium source precursor, and the pH value was controlled to form a gel. Then, pre-carbonization, alkali activation and high-temperature calcination were carried out, followed by acid washing to remove impurities. This process achieved uniform molecular-level dispersion of TiC in the porous carbon, improving conductivity and mechanical strength.

Benefits of technology

Porous carbon materials with high specific surface area, good electrical conductivity and mechanical strength were obtained, avoiding pore collapse during high-temperature calcination and enhancing the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120841514A_ABST
    Figure CN120841514A_ABST
Patent Text Reader

Abstract

The invention discloses composite TiC porous carbon as well as a preparation method and application thereof, and belongs to the technical field of preparation of porous carbon materials. A preparation method of composite TiC porous carbon comprises the following steps: S1, mixing a phenolic compound, an aldehyde compound and an alcoholic solution, dropwise adding tetrabutyl peptidic acid, then adding a pH regulator to regulate the pH value to be alkaline, and stirring to obtain gel; s2, cleaning, drying, low-temperature calcining and crushing the gel to obtain dry powder; mixing the dry powder with alkali, and performing high-temperature activation; s3, the activated dry powder is subjected to acid pickling treatment, then washed to be neutral and dried; and S4, carrying out high-temperature calcination on the dried dry powder, and cooling to obtain the TiC-compounded porous carbon. According to the preparation method of the composite TiC porous carbon, molecular-level dispersion is realized through in-situ polymerization, so that uniform distribution of TiC in the porous carbon is ensured, and the overall mechanical strength and conductivity of the porous carbon are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of porous carbon material preparation technology, and in particular to a porous carbon composite TiC, its preparation method, and its application. Background Technology

[0002] Vapor-deposited silicon-carbon is currently the mainstream silicon-carbon product, and porous carbon, as its core material, directly affects the electrochemical performance of silicon-carbon materials. Phenolic resin-based porous carbon raw materials are controllable, with strong controllability of pore structure and a certain specific surface area, but their mechanical strength and conductivity still need to be improved.

[0003] Phenolic resins can be activated with alkali to create pores, enriching the pore structure and obtaining porous carbon with a high specific surface area. Patent CN119143127 A describes a method of mixing resin-based carbon with alkali for activation, followed by acid washing to obtain porous carbon with a high specific surface area. However, the porous carbon prepared by alkali activation did not undergo higher temperature treatment, resulting in less than ideal conductivity. Furthermore, calcination at higher temperatures can easily cause the pore structure to collapse. Patent CN114551891 B utilizes a surface-confined in-situ growth mechanism to prepare a tin disulfide / titanium dioxide / carbon composite material. In this composite material, nano-sized tin disulfide and titanium dioxide are sealed within a porous carbon framework. The combination of the porous carbon framework and titanium dioxide improves the cycle stability and rate performance of tin disulfide. This patent mentions in-situ polymerization of phenolic resin precursors and titanium source precursors, but activation and high-temperature treatment result in a smaller specific surface area and somewhat lacking conductivity. The formed TiO2 also affects the conductivity of the carbon material.

[0004] Titanium carbide (TiC) has advantages such as high hardness and good electrical conductivity. When combined with carbon materials, it can significantly improve their mechanical strength and electrical conductivity. However, existing processes require the separate synthesis of TiC nanoparticles and carbon substrates, which is complex and energy-intensive. Furthermore, TiC nanoparticles tend to agglomerate and have poor dispersibility when combined with carbon substrates. Summary of the Invention

[0005] The present invention aims to provide a method for preparing porous carbon composite TiC by in-situ polymerization; another objective of the present invention is to provide porous carbon rich in three-dimensional channels with embedded TiC nanoparticles.

[0006] This invention discloses a method for preparing porous carbon composite TiC, comprising the following steps:

[0007] S1 Preparation of precursor gel: Phenolic compounds, aldehyde compounds and alcohol solution are mixed, tetrabutyl peptide is added dropwise, and then a pH adjuster is added to adjust the pH to alkaline. Stirring is performed to obtain a gel.

[0008] S2 pre-carbonization: The gel is washed, dried, calcined at low temperature, and pulverized to obtain dry powder; the dry powder is mixed with alkali and then activated at high temperature;

[0009] S3 pickling and impurity removal: The activated dry powder is pickled, then washed with water until neutral, and dried;

[0010] S4 High-Temperature Calcination: The dried powder is calcined at high temperature, and then cooled to obtain porous carbon composite TiC.

[0011] This invention discloses a method for preparing porous carbon with composite TiC. A phenolic resin precursor and an organotitanium source precursor are uniformly dispersed at the molecular level through in-situ polymerization, shortening the contact distance between TiO2 and carbon after carbonization and lowering the TiC formation energy barrier. A high-temperature carbon substrate acts as a reducing agent to generate TiC in one step, solving the problems of difficult TiC dispersion and preparation. The presence of TiC can improve the electrical conductivity and mechanical strength of porous carbon. TiC nanoparticles are embedded in the carbon layer, acting like "rivets" to inhibit the shrinkage of the carbon matrix, solving the problem of easy pore collapse during high-temperature calcination of porous carbon.

[0012] In step S2, the gel can be washed with ethanol or deionized water; the drying temperature is 60-80℃.

[0013] In step S2, the purpose of mixing the dry powder with alkali and then activating it at high temperature is to optimize the pore structure.

[0014] In step S3, an acid treatment is performed using a 0.5-1 mol / L hydrochloric acid solution.

[0015] Furthermore, in step S1, the phenolic compound includes one or more of phenol, hydroquinone, catechol, and resorcinol; the aldehyde compound includes one of formaldehyde, paraformaldehyde, paraformaldehyde, acetaldehyde, and propionaldehyde; and the mass ratio of the phenolic compound to the aldehyde compound is 1:(1-2).

[0016] Furthermore, in step S1, the alcohol solution is one or more of ethanol, isopropanol, propylene glycol, and butanol; the mass ratio of the alcohol solution to the phenolic compound is (1-4):1.

[0017] Furthermore, in step S1, the mass ratio of the tetrabutyl titanate to the mass of the phenolic compound is 1:(2-4).

[0018] Furthermore, in step S1, the pH adjuster includes ammonia; the pH adjuster adjusts the pH of the mixture to 8.5-9.0; the mixture is heated to 50-80℃ and stirred for 1-5 hours to obtain a gel.

[0019] Furthermore, in step S2, the low-temperature calcination temperature is 400-600℃, and the calcination time is 1-3h; the D50 of the pulverized dry powder is controlled at 6-8μm.

[0020] Furthermore, in step S2, the mass ratio of the dry powder to the alkali is 1:(1-3); the alkali includes one or two of sodium hydroxide and potassium hydroxide; the high-temperature activation temperature is 800-950℃, and the holding time is 1-3h.

[0021] Furthermore, in step S4, the high-temperature calcination temperature is 1200-1500℃, the holding time is 1-3h, and the heating rate is 5-10℃ / min.

[0022] The present invention also discloses a porous carbon composite TiC, which is prepared by the preparation method described above.

[0023] This invention also discloses an application of porous carbon as described above for the preparation of silicon-carbon anode materials.

[0024] This invention discloses a method for preparing porous carbon with composite TiC. Molecular-level dispersion is achieved through in-situ polymerization to ensure uniform distribution of TiC within the porous carbon and improve the overall mechanical strength of the porous carbon. The pore structure of the porous carbon is enriched through a sequential activation method of "in-situ polymerization-pre-carbonization-activation-acid washing-high temperature calcination" to obtain porous carbon with high specific surface area. At the same time, the presence of TiC prevents the collapse of the pore structure of the porous carbon during high temperature and improves the conductivity of the porous carbon. Attached Figure Description

[0025] Figure 1 This is a scanning electron microscope image of the porous carbon composite TiC obtained in Example 1 of this invention;

[0026] Figure 2 This is the N2 adsorption-desorption curve of the porous carbon of composite TiC prepared in Example 1 of this invention. Detailed Implementation

[0027] To make the technical solution of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0028] Example 1

[0029] Preparation of porous carbon composites with TiC:

[0030] S1 in-situ polymerization preparation of precursor gel: 150g of resorcinol and 180g of formaldehyde were added sequentially to a mixture of 300mL of anhydrous ethanol and butanol (the volume ratio of anhydrous ethanol to butanol was 1:1, and the density of the mixture was 0.8g / mL). 50mL of tetrabutyl titanate (TBT) (density 1g / mL) was slowly added dropwise. After the addition was completed, 15mL of ammonia water was added (the pH was controlled at 8.5-9 during the process). The mixture was stirred at 70℃ for 3h to obtain the gel.

[0031] S2 Pre-carbonization treatment: The gel obtained in step S1 was washed with deionized water, dried at 60°C, and then placed in a CVD rotary kiln. The kiln speed was 0.5 r / min, and the temperature was increased to 500°C at 5°C / min. After holding at this temperature for 1.5 h, the gel was removed and pulverized to obtain a dry powder (D50 controlled at 8 μm). The dry powder and KOH were mixed evenly at a mass ratio of 1:2 and then placed in a CVD rotary kiln. The kiln speed was 0.8 r / min, and the temperature was increased to 900°C at 5°C / min. After holding at this temperature for 2 h, the dry powder was obtained.

[0032] S3 Acid Washing and Impurity Removal: The dry powder obtained in step S2 is washed with 0.5 mol / L HCl and then washed with water until neutral. It is then dried at 80°C to obtain dry powder.

[0033] S4 High-temperature calcination: The dry powder obtained in step S3 is placed in a tube furnace and heated to 1400℃ at a heating rate of 10℃ / min. After holding at this temperature for 2 hours, the temperature is lowered to obtain porous carbon material with composite TiC.

[0034] The porous carbon material with composite TiC obtained in Example 1 was subjected to scanning electron microscopy and N2 adsorption tests, and the results are as follows: Figure 1-Figure 2 As shown.

[0035] like Figure 1 As shown, the porous carbon material with composite TiC obtained in Example 1 has an overall blocky structure. Figure 2 As shown, the adsorption curve is type I, and the pore structure is mainly microporous. The porous carbon material of composite TiC obtained in Example 1 is rich in three-dimensional channels.

[0036] Example 2

[0037] Preparation of porous carbon composites with TiC:

[0038] S1 in-situ polymerization preparation of precursor gel: 160g of resorcinol and 200g of formaldehyde were added sequentially to a mixture of 350mL of ethanol and butanol (the volume ratio of ethanol to butanol was 1:1), and 50mL of tetrabutyl titanate (TBT) was slowly added dropwise. After the addition was completed, 15mL of ammonia water was added (the pH was controlled at 8.5-9 during the process), and the mixture was stirred at 80℃ for 2h to obtain the gel.

[0039] S2 Pre-carbonization treatment: The gel obtained in step S1 was washed with deionized water, dried at 70°C, and then placed in a CVD rotary kiln. The kiln speed was 0.8 r / min, and the temperature was increased to 480°C at 8°C / min. After holding at this temperature for 2 hours, the gel was removed and pulverized to obtain dry powder (D50 controlled at 7.5 μm). The dry powder and KOH were mixed evenly at a mass ratio of 1:1.5 and then placed in a CVD rotary kiln. The kiln speed was 1 r / min, and the temperature was increased to 950°C at 5°C / min. After holding at this temperature for 2 hours, the dry powder was obtained.

[0040] S3 Acid Washing and Impurity Removal: The dry powder obtained in step S2 is washed with 0.5 mol / L HCl, then washed with deionized water until neutral, and dried at 60℃ to obtain dry powder.

[0041] S4 High-Temperature Calcination: The dry powder is placed in a tube furnace and heated to 1400℃ at a heating rate of 10℃ / min. After holding at this temperature for 1.5h, the temperature is lowered to obtain porous carbon material with composite TiC.

[0042] Example 3

[0043] Preparation of porous carbon composites with TiC:

[0044] S1 in-situ polymerization preparation of precursor gel: 150g catechol and 190g paraformaldehyde were added sequentially to a mixture of 400mL ethanol and butanol (the volume ratio of ethanol to butanol was 1:1), and 50mL TBT was slowly added dropwise. After the addition was completed, 18mL ammonia water was added (the pH was controlled at 8.5-9 during the process), and the mixture was stirred at 70℃ for 3h to obtain the gel.

[0045] S2 Pre-carbonization treatment: The gel obtained in step S1 was washed with ethanol, dried at 80℃, and then placed in a CVD rotary furnace. The rotary furnace speed was 0.5 r / min, and the temperature was increased to 600℃ at 5℃ / min. After holding at this temperature for 2 hours, the gel was removed and pulverized to obtain dry powder (D50 controlled at 7.5 μm). The dry powder and NaOH were mixed evenly at a mass ratio of 1:2 and then placed in a CVD rotary furnace. The rotary furnace speed was 0.5 r / min, and the temperature was increased to 950℃ at 10℃ / min. After holding at this temperature for 2 hours, the dry powder was obtained.

[0046] S3 Acid Washing and Impurity Removal: The dry powder obtained in step S2 is washed with 0.5 mol / L HCl solution, then washed with deionized water until neutral, and dried to obtain dry powder.

[0047] S4 High-Temperature Calcination: The dry powder is placed in a tube furnace and heated to 1300℃ at a heating rate of 7℃ / min. After holding at this temperature for 2 hours, the temperature is lowered to obtain porous carbon material with composite TiC.

[0048] Example 4

[0049] Preparation of porous carbon composites with TiC:

[0050] S1 in-situ polymerization preparation of precursor gel: 140g hydroquinone and 170g acetaldehyde were added sequentially to a mixture of 400mL ethanol and butanol (the volume ratio of ethanol to butanol was 1:1), 50mL TBT was slowly added dropwise, and after the addition was completed, 18mL ammonia water was added (the pH was controlled at 8.5-9 during the process), and the mixture was stirred at 75℃ for 2.5h to obtain the gel.

[0051] S2 Pre-carbonization treatment: The gel obtained in step S1 was washed with deionized water, dried at 80℃, and then placed in a CVD rotary furnace at a rotation speed of 0.8 r / min. The temperature was increased to 550℃ at a rate of 5℃ / min and held for 2 hours. After holding, the gel was removed and pulverized to obtain dry powder B (D50 controlled at 8μm). The dry powder and NaOH were mixed evenly at a mass ratio of 1:2.5 and then placed in a CVD rotary furnace at a rotation speed of 1.2 r / min. The temperature was increased to 800℃ at a rate of 5℃ / min and held for 2 hours to obtain dry powder.

[0052] S3 Acid Washing and Impurity Removal: The dry powder obtained in step S2 is washed with 0.5 mol / L HCl, then washed with water until neutral, and dried to obtain dry powder.

[0053] S4 High-temperature calcination: The dry powder from step S3 is placed in a tube furnace and heated to 1350℃ at a heating rate of 10℃ / min. After holding at this temperature for 2 hours, the temperature is lowered to obtain porous carbon material with composite TiC.

[0054] Comparative Example 1

[0055] (1) Add 150g of m-diphenol and 180g of formaldehyde to a mixture of 300mL of ethanol and butanol (the volume ratio of ethanol to butanol is 1:1), slowly add 50mL of TBT, and after the addition is complete, add 15mL of ammonia (control the pH to 8.5-9 during the process), stir at 70℃ for 3h to obtain a gel.

[0056] (2) The gel obtained in step (1) was washed with deionized water, dried at 80°C, and then placed in a CVD rotary kiln. The rotary kiln speed was 0.5 r / min, and the temperature was increased to 500°C at 5°C / min. After holding at this temperature for 1.5 h, the gel was removed and pulverized to obtain dry powder (D50 controlled at 8 μm). The dry powder and KOH were mixed evenly at a mass ratio of 1:2 and then placed in a CVD rotary kiln. The rotary kiln speed was 0.8 r / min, and the temperature was increased to 900°C at 5°C / min. After holding at this temperature for 2 h, the dry powder was obtained.

[0057] (3) The dry powder obtained in step (2) is washed with 0.5 mol / L HCl, then washed with deionized water until neutral, and dried to obtain porous carbon material.

[0058] Comparative Example 2

[0059] (1) Add 150g of phenolic resin to a mixture of 300mL of ethanol and butanol (the volume ratio of ethanol to butanol is 1:1), slowly add 50mL of TBT, and after the addition is complete, add 15mL of ammonia water (control the pH to 8.5-9 during the process), stir at 70℃ for 3h to obtain gel.

[0060] (2) The gel from step (1) was washed with deionized water, dried at 80°C, and then placed in a CVD rotary kiln. The rotary kiln speed was 0.5 r / min, and the temperature was increased to 500°C at a rate of 5°C / min. After holding at this temperature for 1.5 h, the gel was removed and pulverized to obtain dry powder (D50 controlled at 8 μm). The dry powder and KOH were mixed evenly at a mass ratio of 1:2 and then placed in a CVD rotary kiln. The rotary kiln speed was 0.8 r / min, and the temperature was increased to 900°C at a rate of 5°C / min. After holding at this temperature for 2 h, the dry powder was obtained.

[0061] (3) The dry powder in step (2) is washed with 0.5 mol / L HCl, then washed with deionized water until neutral, and dried to obtain dry powder.

[0062] (4) Place the dry powder in a tube furnace and heat it to 1400℃ at 10℃ / min. After holding it at that temperature for 2 hours, cool it down to make it a porous carbon material.

[0063] Comparative Example 3

[0064] (1) Add 150g of m-diphenol and 180g of formaldehyde to a mixture of 300mL of ethanol and butanol (the volume ratio of ethanol to butanol is 1:1), add 15mL of ammonia (control the pH to 8.5-9 during the process), stir at 70℃ for 3h to obtain a gel.

[0065] (2) The gel obtained in step (1) was washed with deionized water, dried at 60°C and placed in a CVD rotary oven. The rotary oven speed was 0.5 r / min, and the temperature was increased to 500°C at 5°C / min. After holding at the temperature for 1.5 h, it was taken out and pulverized to obtain dry powder (D50 controlled at 8 μm).

[0066] (3) The dry powder obtained in step (2) and KOH are mixed evenly at a mass ratio of 1:2 and then placed in a CVD rotary furnace. The rotary furnace speed is 0.8 r / min, and the temperature is increased to 900℃ at 5℃ / min. After holding at the temperature for 2 hours, the dry powder is obtained.

[0067] (4) The dry powder obtained in step (3) is washed with 0.5 mol / L HCl, then washed with deionized water until neutral, and dried to obtain dry powder.

[0068] (5) Place the dry powder in a tube furnace, heat it to 1400℃ at 10℃ / min, keep it at the temperature for 2 hours and then cool it down to obtain porous carbon material.

[0069] Comparative Example 4

[0070] (1) Add 150g of m-diphenol and 180g of formaldehyde to a mixture of 300mL of ethanol and butanol (the volume ratio of ethanol to butanol is 1:1), slowly add 50mL of TBT, and after the addition is complete, add 15mL of ammonia (control the pH to 8.5-9 during the process), stir at 70℃ for 3h to obtain a gel.

[0071] (2) The gel in step 1) was washed with deionized water, dried at 80°C and placed in a CVD rotary oven. The rotary oven speed was 0.5 r / min, and the temperature was increased to 500°C at 5°C / min. After holding at the temperature for 1.5 h, it was taken out and pulverized to obtain dry powder (D50 controlled at 8 μm).

[0072] (3) The dry powder obtained in step (2) and KOH are mixed evenly at a mass ratio of 1:2 and then placed in a CVD rotary furnace. The rotary furnace speed is 0.8r / min, the temperature is increased to 900℃ at 5℃ / min, and the dry powder is obtained after holding for 2h.

[0073] (4) Place the dry powder obtained in step (3) in a tube furnace, heat it to 1400℃ at 10℃ / min, keep it at the temperature for 2 hours and then cool it down to obtain porous carbon material.

[0074] Performance testing:

[0075] The porous carbon obtained in Examples 1-4 and Comparative Examples 1-4 was tested for specific surface area, electrical conductivity, and compressive strength. The test results are shown in Table 1. Specific surface area was obtained through adsorption-desorption curves, electrical conductivity was obtained using a conductivity meter at 50 MPa, and compressive strength was obtained using a nanoindentation apparatus.

[0076] Table 1. Test results of the physicochemical properties of porous carbon materials

[0077] <![CDATA[Specific surface area (m 2 / g)]]> Electrical conductivity (S / cm) Compressive strength (GPa) Example 1 2070.1 1.65 3.53 Example 2 1896.5 1.92 3.12 Example 3 1962.8 1.86 3.28 Example 4 2126.4 1.72 3.66 Comparative Example 1 1912.3 0.63 2.16 Comparative Example 2 1822.6 0.96 2.35 Comparative Example 3 1642.3 0.90 1.42 Comparative Example 4 1638.6 0.72 2.22

[0078] As shown in Table 1, Examples 1-4 exhibit larger specific surface area, higher electrical conductivity, and higher mechanical strength compared to Comparative Examples 1-4. The higher electrical conductivity and mechanical strength of Example 1 compared to Comparative Example 1 are mainly due to the fact that high-temperature calcination in Example 1 reduces crystal defects in the carbon material, leading to a more ordered arrangement of carbon atoms and thus improving conductivity. Meanwhile, Comparative Example 1, lacking high-temperature calcination, primarily generated TiO2 from the titanium source, which also affected the mechanical strength and electrical conductivity of the carbon material.

[0079] Compared to Comparative Example 2, Example 1 showed improvements in specific surface area, electrical conductivity, and mechanical strength. This was mainly because in Comparative Example 2, the phenolic resin and titanium source were directly mixed, which could lead to uneven dispersion and uneven TiC formation in the high-temperature section, resulting in local pore collapse and affecting the overall electrical conductivity and mechanical strength.

[0080] Compared with Comparative Example 3, Example 1 showed a significant improvement in specific surface area, electrical conductivity, and mechanical strength. This was mainly because Comparative Example 3 did not introduce a titanium source, and high-temperature calcination caused the pore structure to collapse, which severely affected the specific surface area and electrical conductivity. At the same time, the mechanical strength of the carbon layer itself was relatively low.

[0081] Compared with Comparative Example 4, Example 1 showed a significant improvement in specific surface area, electrical conductivity, and mechanical strength. This was mainly because Comparative Example 4 was not acid-washed, and the residual potassium salt melted at high temperature, blocking the pores and reducing the specific surface area. This also affected the overall electrical conductivity and mechanical strength of the carbon material.

[0082] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.

Claims

1. A method for preparing porous carbon composite TiC, characterized in that, Includes the following steps: S1 Preparation of precursor gel: Phenolic compounds, aldehyde compounds and alcohol solution are mixed, tetrabutyl peptide is added dropwise, and then a pH adjuster is added to adjust the pH to alkaline. Stirring is performed to obtain a gel. S2 pre-carbonization: The gel is washed, dried, calcined at low temperature, and pulverized to obtain dry powder; the dry powder is mixed with alkali and then activated at high temperature; S3 pickling and impurity removal: The activated dry powder is pickled, then washed with water until neutral, and dried; S4 High-Temperature Calcination: The dried powder is calcined at high temperature, and then cooled to obtain porous carbon composite TiC.

2. The porous carbon composite TiC according to claim 1, characterized in that, In step S1, the phenolic compound includes one or more of phenol, hydroquinone, catechol, and resorcinol; the aldehyde compound includes one of formaldehyde, paraformaldehyde, paraformaldehyde, acetaldehyde, and propionaldehyde; and the mass ratio of the phenolic compound to the aldehyde compound is 1:1-2.

3. The porous carbon composite TiC according to claim 1, characterized in that, In step S1, the alcohol solution is one or more of ethanol, isopropanol, propylene glycol, and butanol; the mass ratio of the alcohol solution to the phenolic compound is 1-4:

1.

4. The porous carbon composite TiC according to claim 1, characterized in that, In step S1, the mass ratio of the tetrabutyl titanate to the phenolic compound is 1:2-4.

5. The porous carbon composite TiC according to claim 1, characterized in that, In step S1, the pH adjuster includes ammonia; the pH adjuster adjusts the pH of the mixture to 8.5-9.0; the mixture is heated to 50-80℃ and stirred for 1-5 hours to obtain a gel.

6. The porous carbon composite TiC according to claim 1, characterized in that, In step S2, the low-temperature calcination temperature is 400-600℃ and the calcination time is 1-3h; the D50 of the dry powder obtained by pulverization is controlled at 6-8μm.

7. The porous carbon composite TiC according to claim 1, characterized in that, In step S2, the mass ratio of the dry powder to the alkali is 1:1-3; the alkali includes one or two of sodium hydroxide and potassium hydroxide; the high-temperature activation temperature is 800-950℃, and the holding time is 1-3h.

8. The porous carbon composite TiC according to claim 1, characterized in that, In step S4, the high-temperature calcination temperature is 1200-1500℃, the holding time is 1-3h, and the heating rate is 5-10℃ / min.

9. A porous carbon composite of TiC, characterized in that, It is prepared by the preparation method described in any one of claims 1-8.

10. An application of porous carbon as described in claim 9, characterized in that, Used to prepare silicon-carbon anode materials.

Citation Information

Patent Citations

  • A tin disulfide / titanium dioxide / carbon composite material, its preparation method and application

    CN114551891B

  • Alkali-activated porous carbon and preparation method thereof

    CN119143127A